APLIKASI PENGOLAHAN DATA PASIEN STUDI KASUS RSUD SAWERIGADING PALOPO SULAWESI SELATAN - Abdul Haris; Alan Burhan (Sekolah Tinggi Teknik - PLN, 2015)
Currently the Hospital Sawerigading Palopo still using manual systems in data processinginpatients and outpatients, the data processing system are now experiencing difficulties in findingthe necessary patient data so it takes a long time. In addition the processing of patient data with thecurrent system does not have a good reporting system, so we need a new system, which canovercome these problems. Therefore, Sawerigading Regional General Hospital (HospitalSawerigading) require patient data processing applications that are capable of handling a varietyof obstacles above. Applications will facilitate the processing of patient data to hospital officials indata processing and printing patient reporting of patient data.